2013
DOI: 10.1186/2045-9912-3-21
|View full text |Cite
|
Sign up to set email alerts
|

Cold Atmospheric Plasma: methods of production and application in dentistry and oncology

Abstract: Cold Atmospheric Plasma is an ionized gas that has recently been extensively studied by researchers as a possible therapy in dentistry and oncology. Several different gases can be used to produce Cold Atmospheric Plasma such as Helium, Argon, Nitrogen, Heliox, and air. There are many methods of production by which cold atmospheric plasma is created. Each unique method can be used in different biomedical areas. In dentistry, researchers have mostly investigated the antimicrobial effects produced by plasma as a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
191
0
3

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 328 publications
(223 citation statements)
references
References 122 publications
2
191
0
3
Order By: Relevance
“…As previously mentioned, CAP is also used for anticancer therapy [20][21][22][23]. Vitamin C has also been suggested to have adverse effects on cancer cells [28].…”
Section: Combining Vitamin C With Cold Atmospheric Plasmamentioning
confidence: 99%
See 2 more Smart Citations
“…As previously mentioned, CAP is also used for anticancer therapy [20][21][22][23]. Vitamin C has also been suggested to have adverse effects on cancer cells [28].…”
Section: Combining Vitamin C With Cold Atmospheric Plasmamentioning
confidence: 99%
“…Interestingly, CAP is also being studied in oncology to eradicate tumor cells. It has been demonstrated that cold plasma can induce necrosis, apoptosis and cell detachment by disrupting certain phases of tumor cell replication [20]. CAP effectiveness has been demonstrated against dozens of tumor cell lines and tumor types in vitro and in vivo, respectively [21].…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…humidity, gas temperature and pressure. Exposure of the bacterial samples to the plasma glow is always more effective than exposure to plasma afterglow as in the plasma glow the short-living species as well as longliving species have a high probability to reach the treated sample [23].…”
Section: Discussionmentioning
confidence: 99%
“…NTP has electrons at a hotter temperature than the heavy particles that are at room temperature which are usually in helium, argon, nitrogen, helium and air. 14 The method of plasma treatment advances the surface adaptation of dental materials. 15 In the previous studies, it is reported that surface modification using plasma treatment have improved the bonding strength between heat cured acrylic resin and self-curing acrylic resin.…”
Section: 대한치과보철학회지 56권 3호 2018년 7월mentioning
confidence: 99%